Fucoxanthin Prevents 6-OHDA-Induced Neurotoxicity by Targeting Keap1. (11th March 2021) - Wu, Wei; Han, Hui; Liu, Jingwangwei; Tang, Min; Wu, Xiaoyu; Cao, Xiaojun; Zhao, Tiantian; Lu, Yujia; Niu, Tingting; Chen, Juanjuan; Chen, Haimin
Abstract : As the most abundant marine carotenoid extracted from seaweeds, fucoxanthin (FUC) is considered to have excellent neuroprotective activity. However, the target of FUC for its neuroprotective properties remains largely unclear. Oxidative stress is one of the initiating factors causing neuronal cell loss and necrosis, and it is also an important inducement of Parkinson's disease (PD). In the present study, the neuroprotective effect of FUC was assessed using a 6-hydroxydopamine- (6-OHDA-) induced neurotoxicity model. FUC suppressed 6-OHDA-induced accumulation of intracellular ROS, the disruption of mitochondrial membrane potential, and cell apoptosis through the Nrf2-ARE pathway. Keap1 as a repressor of Nrf2 can regulate the activity of Nrf2. Here, the biolayer interferometry (BLI) assay demonstrated that FUC specifically targeted Keap1 and inhibited the interaction between Keap1 and Nrf2. FUC bound to the hydrophobic region of Keap1 pocket and formed hydrogen bonding interactions with Arg 415 and Tyr 525 . Besides, it also dose-dependently upregulated the expressions of antioxidant enzymes, such as nicotinamide heme oxygenase-1, glutamate-cysteine ligase modifier subunit, and glutamate-cysteine ligase catalytic subunit, in 6-OHDA-induced PC12 cells. In 6-OHDA-exposed zebrafish, FUC pretreatment significantly increased the total swimming distance of zebrafish larvae and improved the granular region of the brain tissue damage. These results suggested that FUC could protect the neuronal cells against 6-OHDA-induced injury via targeting Keap1.